A construção do sentido pela adjetivação em publicidades - Scolari, Natali (2014)
This dissertation aims to investigate the production of meaning by the use of adjectives in the discourse of advertising by means of a semantic-linguistic approach. This work is based on the Theory of Argumentation within Language, by Oswald Ducrot and Jean-Claude Anscombre, and its most recent version, the Theory of Semantic Blocks, by O. Ducrot and Marion Carel. Both theories explain how meaning is built through a linguistic perspective, disregarding factors external to language. Argumentation is conceived as the construction of meaning by a speaker who produces discourse by using the words of language. The Theory of Semantic Blocks classifies adjectives as operators, which may perform in discourse as modifiers or internalizers. Adjectives operate in discourse by modifying the value of a term, either by acting on its graduality or reorganizing the words that constitute this term. In this study we investigated how an adjective may relate to other components in the discourse through the analysis of the argumentative value of the adjective in the characterization and description of the products presented in advertisement. The corpus of this research is composed of a selection of advertisements published in Portuguese by Brazilian magazines. The results of our analyses indicate the performance of adjectives as modifiers of the word they are applied to, as well as modifiers of discourse. Thus, adjectives partake in the construction of the argumentation that corroborates the speaker s subjective and intersubjective point of view.